Prevalence, Comorbidities, and Risk of Perioperative Complications in Human Immunodeficiency Virus-Positive Patients Undergoing Cervical Spine Surgery. Issue 21 (November 2015) - Lovy, Andrew J.; Guzman, Javier Z.; Skovrlj, Branko; Cho, Samuel K.; Hecht, Andrew C.; Qureshi, Sheeraz A.
Abstract : Study Design: Retrospective database analysis. Objective: To evaluate outcomes of human immunodeficiency virus (HIV) positive patients after cervical spine surgery. Summary of Background Data: Highly active antiretroviral medications have qualitatively altered the natural history of HIV, thus increasing the number of HIV-positive patients seeking treatment for chronic degenerative conditions. Minimal data exist on HIV patients undergoing degenerative cervical spine surgery. Methods: The Nationwide Inpatient Sample was examined from 2002 to 2011. Hospitalizations were identified using International Classification of Diseases Ninth Revision, Clinical Modification (ICD-9-CM) procedural codes for cervical spine surgery and diagnoses codes for degenerative conditions of the cervical spine, and HIV. Statistical analysis was conducted to evaluate associations between HIV status and perioperative complications. Results: A total of 1, 602, 129 patients underwent degenerative cervical spine surgery, of which 3700 patients (0.23%) had HIV. The prevalence of HIV increased over the study period from 0.19% to 0.33% ( P  < 0.001). Patients with HIV were younger (48.6 yrs vs. 53.4 yrs, P  < 0.001) and more likely to be male ( P  < 0.001). HIV patients had significantly greater odds of having chronic pulmonary disease, liver disease, and drug abuse. Unadjusted analysis did not reveal increased rate of acute complications among HIV-positive patients compared with negative controls (3.8% vs. 3.7%, P  = 0.62). Multivariate analysis did not identify HIV as a significant predictor of complication (odds ratio = 1.04, P  = 0.84). HIV was associated with a 1.5 day increased length of stay AND 1.29 fold increase in median costs compared with controls ($14, 551 vs. 18, 846, P  < 0.001). Conclusion: The prevalence of HIV patients undergoing degenerative cervical spine surgery is increasing. A diagnosis of HIV was not associated with an increased risk of perioperative complication among patients undergoing degenerative cervical spine surgery. Further clinical studies are needed to evaluate predictors of complications among HIV patients and long-term outcomes. Level of Evidence: 4